2014
DOI: 10.1002/da.22249
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Threshold for a Clinically Relevant Effect? The Case of Major Depressive Disorders

Abstract: Statistical outcomes cannot be equated with clinical relevance. The "MID" may be used for pinpointing the cutoff for clinical relevance, but more work in this area is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
135
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(148 citation statements)
references
References 21 publications
3
135
1
1
Order By: Relevance
“…In a meta-analysis of psychodynamic therapy (PDT) including different mental disorders, Steinert et al (2017) chose a margin of g = 0.25, which is among the smallest margins ever used in psychotherapy and medical research (Gladstone andVach, 2014, Figure 2, Steinert et al, 2017, p. 944). This margin is very close to both (a) the threshold for a minimally important difference specifically suggested for depression (0.24, Cuijpers et al, 2014), and (b) the margin recommended by Gladstone and Vach (2014) to protect against degradation of treatment effects in non-inferiority trials (d = −0.23).…”
Section: Equivalence and Non-inferiority Marginssupporting
confidence: 75%
“…In a meta-analysis of psychodynamic therapy (PDT) including different mental disorders, Steinert et al (2017) chose a margin of g = 0.25, which is among the smallest margins ever used in psychotherapy and medical research (Gladstone andVach, 2014, Figure 2, Steinert et al, 2017, p. 944). This margin is very close to both (a) the threshold for a minimally important difference specifically suggested for depression (0.24, Cuijpers et al, 2014), and (b) the margin recommended by Gladstone and Vach (2014) to protect against degradation of treatment effects in non-inferiority trials (d = −0.23).…”
Section: Equivalence and Non-inferiority Marginssupporting
confidence: 75%
“…Still, it should be noted that when comparing antidepressive medications with placebo alone, effect sizes cannot provide sufficient information on the clinical relevance of treatment effects in individual clinical contexts, so this issue is likely to remain controversial. 9,38 The results of our analyses indicate that antidepressants have higher short-term effects when compared with placebo also in primary care.…”
Section: Discussionmentioning
confidence: 84%
“…It is not clear what the threshold for a clinically significant effect size is for treatments in depression, but in an earlier paper, we showed that an effect size of d=0.24 could be considered as a ‘minimally important difference’ as seen from the patient perspective 6. We will use this as the threshold for a clinical significant difference between treatments.…”
Section: The First Step: Statistical Power Of Individual Trialsmentioning
confidence: 97%